2001
DOI: 10.1128/jvi.75.14.6440-6449.2001
|View full text |Cite
|
Sign up to set email alerts
|

Role of the 3′-Untranslated Regions of Alfalfa Mosaic Virus RNAs in the Formation of a Transiently Expressed Replicase in Plants and in the Assembly of Virions

Abstract: Alfalfa mosaic virus (AMV) RNAs 1 and 2 encode the replicase proteins P1 and P2, respectively, whereas RNA 3 encodes the movement protein and the coat protein (CP). When RNAs 1 and 2 were transiently expressed from a T-DNA vector (R12 construct) by agroinfiltration of Nicotiana benthamiana, the infiltrated leaves accumulated minus-strand RNAs 1 and 2 and relatively small amounts of plus-strand RNAs. In addition, RNA-dependent RNA polymerase (RdRp) activity could be detected in extracts of the infiltrated leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
76
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 66 publications
(90 reference statements)
3
76
0
Order By: Relevance
“…Infiltration of N. benthamiana leaves with a mixture of Agrobacterium tumefaciens clones containing pMOGR12 and pMOGR3 results in accumulation of viral RNA and protein at the level of a wt AMV infection (31). pMOGR3 carries a 35S expression cassette containing cDNA 3 in its T region (31).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Infiltration of N. benthamiana leaves with a mixture of Agrobacterium tumefaciens clones containing pMOGR12 and pMOGR3 results in accumulation of viral RNA and protein at the level of a wt AMV infection (31). pMOGR3 carries a 35S expression cassette containing cDNA 3 in its T region (31).…”
mentioning
confidence: 99%
“…In the present study, the 5Ј UTR of RNA 1 (L1) was replaced with the 5Ј UTR of RNA 2 (L2) or RNA 3 (L3). The mutations were introduced into pBSR1, which contains a DNA copy of RNA 1 cloned between a cauliflower mosaic virus 35S promoter and the terminator of the nopaline synthase gene (31). To that end, sequences containing L2 or L3 downstream of a 35S promoter were transferred to pBSR1 from pCA27T-Nco or pCA35T-Nco using KpnI and NcoI.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We do not think this effect is significant enough to support the model of the Gehrke lab, which states that low amounts of CP actually favor minus-strand synthesis (9). Previous experiments have shown that minusstrand RNA3 synthesis and plus-strand RNA4 synthesis can be perfectly carried out using a CP-free polymerase (5,10,28). Addition of CP to reactions with CP-free polymerase was found to block minus-strand synthesis.…”
Section: Discussionmentioning
confidence: 59%